Upconversion superballs for programmable photoactivation of therapeutics - Zhen Zhang (Nature Portfolio, 2019)
The synthesis of nanoparticles capable of orthogonal photo-activity is complex. Here, the authors report on an assembly process of two distinct nanoparticles into composite nanoparticles as a simple method and report on the application in photodynamic therapy and siRNA delivery in tumour therapy.